SERVICE QUALITY IMPROVEMENT STRATEGIES IN THE USE AND SECURITY OF MOBILE BANKING FROM THE PERSPECTIVE OF MASLAHAH MURSALAH AMONG BANK MANDIRI CUSTOMERS IN THE JEMBER AREA - Lutfia Farhatul Mahmuda; Misbahul Munir; Siti Masrohatin (Adisam Publisher, 2025)
This study aims to explore strategies for improving service quality in the use and security of mobile banking from the perspective of Maslahah Mursalah among Bank Mandiri customers in the Jember area. The concept of Maslahah Mursalah, which emphasizes public interest and welfare, serves as a theoretical foundation to evaluate how service quality enhancement can align with customers’ needs and security concerns. Using a qualitative approach, data were collected through in-depth interviews and surveys involving Bank Mandiri customers actively using mobile banking services. The findings reveal that customers prioritize ease of use, transaction security, and responsive customer support as critical factors for service quality improvement. Furthermore, the study identifies several strategic measures, such as implementing advanced encryption technology, enhancing user education on mobile security, and optimizing application interfaces to increase trust and satisfaction. This research contributes to both academic knowledge and practical applications by integrating Islamic ethical principles with contemporary banking service quality management. The results recommend that banks consider the Maslahah Mursalah framework to foster better customer relations, reduce security risks, and promote sustainable mobile banking usage. This approach not only strengthens financial inclusion but also ensures that technological advancements respect the welfare and security of all stakeholders.